UMPSA receives visit from Director-General of Public Works - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 26 January 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) received a visit from the Director-General of Public Works, Datuk Wira Ir. Roslan Ismail, who was accompanied by a delegation from the Public Works Department (JKR) to strengthen collaboration between JKR and UMPSA.